Improved electrodeposition of CdS layers in presence of activating H2SeO3 microadditive. (1st November 2016) - Maricheva, J.; Bereznev, S.; Naidu, R.; Maticiuc, N.; Mikli, V.; Kois, J.
ABSTRACT: CdS thin films were deposited electrochemically onto indium tin oxide (ITO)/glass substrates from aqueous solutions containing 0.01 M CdCl2, 0.05 M Na2 S2 O3 and 0.02 M Edta-Na2 at −1.2 mV versus saturated sulfate reference electrode. Depositions were carried out at various temperatures (20, 50 and 80 °С) and different pH (2.5, 3.5 and 4.5) in a three electrode electrochemical cell. All above mentioned electrochemical syntheses were reproduced in presence of H2 SeO3 microadditive to compare resulted CdS layers. Electrodeposited CdS thin films were characterized by different instrumental techniques to know the influence of deposition conditions on the quality of the obtained layers. It was found that the presence of 0.05–0.5 mM of H2 SeO3 in the electrolyte changes the mechanism of the CdS film formation that facilitates nucleation and a growth of a more dense and uniform polycrystalline CdS film. Addition of 0.5 mM of H2 SeO3 into the initial solution allowed us to obtain nearly stoichiometric (sulfur content ~52 at%) CdS films at reduced temperature value of 50 °C vs. higher temperature values used in a conventional electrodeposition process of CdS layers. No Se-containing phases were detected by EDX, Raman and XRD analyses in the CdS films. The presence of H2 SeO3 tends to rearrange polytype crystalline structure of CdS to more stable hexagonal structure. The band gap value of CdS was increased from 2.3 eV to 2.5 eV as a result of H2 SeO3 addition. Highlights: Improved technology of electrodeposition of stoichiometric CdS thin films based on H2 SeO3 microadditive. Studies of H2 SeO3 influence on the mechanism of electrochemical formation of CdS thin films in acidic medium. Modification of crystalline structure, morphology and optical properties of the CdS thin films in the presence of H2 SeO3.